Comparative Analysis between Rabin Karp Algorithm, Winnowing, and Turnitin Applications for Detecting Plagiarized Words - Ari Kurniawan Saputra; Kurnia Muludi; Taqwan Thamrin (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Plagiarism was considered to violate the law because it copied of other people's works. To prevent plagiarism in terms of scientific writing, every word or sentence of scientific texts had to be detected through word-matching algorithm in the written text. The objective of this study was to compare the accuracy of values between the Rabin Karp Algorithm and the Winnowing Algorithm. The accuracy of values of these algorithms was compared with that of the values of Turnitin application. The data analysis used in this study was Hypothesis T-test. The result of this study was that the value of Rabin Karp Algorithm was higher than that of the Winnowing Algorithm and the Turnitin Application.Keywords: Plagiarisme, Turnitin, Rabin Karp Algorithm, Winnowing Algorithm